좋은 수업을 위한 교육과정 재구성 과정에서 중등 초임 체육교사가 겪는 사고변화 - 제성준, 윤현수 (교과교육학연구, 2015)
이 연구는 좋은 수업을 위한 교육과정 재구성 과정에서 중등 초임체육교사가 겪는 어려움을 밝히고 그것을 해결하기 위해 어떤 노력을 하며 결국에 어떠한 사고변화가 일어나는지 심층적으로 밝히 는데 목적이 있다. 연구 목적을 달성하기 위해서 Strauss와 Corbin(1998)의 근거이론 방법을 채택하 였고 연구참여자 선정은 이론적 표집법에 따라 서울, 경기, 인천 소재의 남녀공학 중학교에 근무하고 있는 교육경력 5년 이하의 초임체육교사 최초 3명을 선정한 후 이론적 포화를 이룰 때 가지 연구참여자를 추가하여 최종 9명을 선정하였다. 20회의 비구조화 된 공식 인터뷰를 중심으로 자료를 수 집하였고 연구와 관련된 문화적 인공물, 문헌연구 자료를 추가 수집하였다. 자료 분석은 Strauss와 Corbin(1998)의 분석절차에 따라 개방코딩, 축코딩, 선택코딩의 절차를 따르면서도 각 코딩 단계를 오가면서 순환적으로 분석하였다. 연구의 진실성은 연구참여자 확인, 다각도 검증, 동료연구자 검 토, 예외 사례 분석을 통해 확보하였다. 결과로서 첫째, 초임 체육교사들은 교육과정을 재구성하는 과정에서 체육 교수내용지식의 부족과 이상과 현실과의 괴리에서 오는 어려움을 겪고 있었다. 둘째, 초임 체육교사들의 어려움 극복 전략으로 자아성찰, 상호교섭, 매체활용하기를 시도하고 있었 다. 셋째, 이러한 과정에서 초임 체육교사들은 체육교육과정에 대한 안목 형성이 형성되고, 체육 교수내용지식은 진화하였으며, 교사 수준 교육과정 재구성의 실천자가 되고 있었다. This study was conducted to identify novice physical education teachers’ difficulties experiencing the teacher level of the curriculum reconstruction for good teaching, and to provide the deeper elucidation of what efforts they make and what process they eventually undergo in order to resolve theses difficulties. For this study, Strauss & Corbin’s (1998) Grounded Theory Methodology was adopted and 9 novice physical education teachers were adopted as the participants, who were working in co-ed junior hight schools and having their experience less than 5 years in teaching. Data were collected centered around 20 times of non-structured formal interviews, and cultural artifacts and literature research materials related to this study were additionally collected. For data analysis, recursive analysis was made by passing through each coding step while following the procedure of open coding, axial coding, and selective coding. Research integrity was established through identification of participants, multifaceted verification, review of co-researchers, and exceptional case analysis. The findings are as follows: First, novice physical education teachers had the difficulties due to the lack of physical education pedagogical content knowledge and to the gap between ideals and reality in the process of curriculum reconstruction. Second, novice physical education teachers were trying to make use of self-reflection, mutual negotiation, and media application as their strategy to overcome the difficulties. Third, this process led to forming an eye for physical education curriculum, the evolution of physical pedagogical content knowledge, and became a practitioner of teacher level curriculum reconstruction. KCI Citation Count: 11